Perceptions and moral distress in surplus embryo disposition among Japanese IVF patients: a qualitative study - Katsuzaki, Shizuka; Takimoto, Yoshiyuki; Morioka, Chikako; Nakayama, Masahiro; Harada, Tatsuya; Urata, Yoko; Ishikawa, Tomonori; Takagi, Masatoshi (Frontiers in Reproductive Health, 2025)
BackgroundThe growing use of in vitro fertilization (IVF) in Japan has led to an increase in surplus frozen embryos and the associated ethical dilemmas. Cultural values, institutional practices, and limited legal guidance contribute to patient distress and uncertainty. However, little is known about how Japanese patients perceive surplus embryos, and how these views relate to their emotional experiences and support preferences.MethodsThis qualitative study included semi-structured interviews with 46 female patients who had undergone IVF recruited from three Japanese fertility clinics with varying policies for embryo disposition. The interviews were conducted online between May 2024 and March 2025. Data were analyzed using thematic analysis guided by Boyatzis's inductive coding method.ResultsParticipants conceptualized embryos in three main ways: as “life,” as genetically connected “blood ties,” or as “cells or eggs.” These perceptions—now more diverse than in earlier reports—influence emotional responses and dispositional decisions. Viewing embryos as life forms is often associated with guilt and sorrow, particularly in the absence of clear information or acceptable options, and could be understood as a form of moral distress from the patient's perspective. Practical considerations, such as storage fees and future family planning, also shaped both perceptions and emotional burden. Gendered responses were observed: women with female-factor infertility tended to internalize blame, while male-factor diagnoses allowed for emotional distancing. Institutional factors, including storage fees, a lack of legal frameworks, and stigma, shape moral distress and decision-making. While embryo donation for research is often preferred, donation to other patients is strongly opposed, reflecting cultural concerns about kinship and genetic identity. Support preferences range from symbolic closures to informal peer dialogues.ConclusionPatient perceptions of surplus embryos are shaped by cultural values, gendered expectations, and institutional factors, and practical constraints. These findings highlight the need for culturally responsive, ethically grounded, and flexible care models that acknowledge moral distress as experienced by patients and the growing diversity in how embryos are conceptualized.